EFEKTIVITAS TEKNIK RELAKSASI DALAM KONSELING KELOMPOK BEHAVIORAL UNTUK MENURUNKAN STRES BELAJAR SISWA SMA - Nurcahyani, Istiana; Fauzan, Lutfi (Jurnal Kajian Bimbingan dan Konseling, 2016)
This research purpose to know the effectiveness of relaxation technique in behavioral group counseling to reducing academic stress at senior high school students. Research use one-group pretest-posttest design. The subject are selected 5 students based on high scores academic stress scale. Instruments used the scale academic stress was developed from various theories stress by Hans Selye (1976), Lazarus and Folkman (1984) with reliability is 0.898 and item validity > 0.3. Data were analyzed using wilcoxon signed ranks test. The analysis showed the Z count value is -2.032 with significance level of 0.042 <0.05 which can be concluded that relaxation techniques effective for reducing academic stress of senior high school students.